Does maternal long chain polyunsaturated fatty acid status in pregnancy influence the bone health of children? The Southampton Women’s Survey - Harvey, Nicholas (2011)
PURPOSE: Maternal diet in pregnancy has been linked to childhood bone mass, but the mechanisms and nutrients involved are uncertain. Long-chain polyunsaturated fatty acids (LCPUFAs) have been shown to affect bone metabolism, but the relationship between maternal fatty acid status and bone mass in the offspring remains unknown. METHODS: We evaluated the association between maternal LCPUFA status in late pregnancy (34 weeks gestation) and bone density in their children at age four years, within 727 mother-child pairs taking part in the Southampton Women’s Survey. RESULTS: Concentrations of the n-3 LCPUFA component of maternal plasma phosphatidylcholine were positively associated with a number of bone mineral measures at the age of 4 years; these associations persisted after adjustment for maternal body build, walking speed and infant feeding. Relationships were most evident for eicosapentaenoic acid (r=0.09, p=0.02 for whole body areal bone mineral density [aBMD] and r=0.1, p=0.008 for lumbar spine aBMD) and for docosapentaenoic acid (r=0.09, p=0.02 for whole body aBMD and r=0.12, p=0.002 for lumbar spine aBMD). CONCLUSIONS: These findings suggest that variation in early exposure to n-3 and n-6 LCPUFA may have potential consequences for bone development and that the effects appear to persist into early childhood.